Circulating tumor stem like cells in oral squamous cell carcinoma: An unresolved paradox. (November 2016) - Patel, Shanaya; Shah, Kavan; Mirza, Sheefa; Shah, Kanisha; Rawal, Rakesh
Highlights: CD44 is identified as circulating tumor stem like cell marker in OSCC. CD44+ cells demonstrated self renewal & chemo-resistance - hallmarks of CSCs. Significant upregulation of CD44v6 and Nanog was observed in OSCC patients. Association of CD44v6 was observed with loco-regional aggressiveness and relapse. CD44v6 could be utilized as prognostic marker to monitor disease progression. Abstract: Objective: Circulating tumor cells (CTCs) are increasingly gaining importance due to their immense potential in enhancing diagnosis, prognosis and response to therapy in solid malignancies. Therefore, we aimed to comprehend the molecular diversity and critical role of this disseminated tumor population in OSCC. Methodology: CD44+ subpopulation was isolated using immuno-magnetic cell separation and their purity was validated using flow cytometry. Characterisation of self renewal potential and resistance to chemotherapy was assessed using tumor sphere forming and cytotoxicity assay. Gene expression profile of pertinent CSC (CD44s, CD44v3, CD44v6) and stemness markers (Bmi1 and Nanog) was carried out in CD44+ cells using Real Time PCR. Predominantly expressed markers and their association with clinico-pathological conditions were substantiated in 30 OSCC patients. Result: Flow cytometry analysis depicted a predominant population of CD44+CD24−CD45− cells suggesting that circulating tumor cells had a subpopulation of CSC like cells in the circulation. These cells demonstrated increased sphere forming capability and intrinsic chemo-resistance compared to non-CSC, thus indicating the CSC features of self-renewal and chemo-resistance. Additionally, CD44+ cells showed significantly increased expression levels of CD44v6 and Nanog compared to CD44− cells. Clinically, expression pattern of CD44v6 and Nanog correlated with different anatomical subsites, loco-regional aggressiveness of the disease and recurrence, thus opening newer avenues that can be explored for better prognostic and therapeutic implications. Conclusion: This study explored the inevitable role of CD44v6 and Nanog as circulating stem like cell markers in assessment of loco-regional aggressiveness, detection of relapse and therapeutic response and resistance.